Hidden Drug Abuse in Hong Kong: From Social Acquaintance to Social Isolation - Tam, Cherry Hau-lin; Kwok, Sharon I.; Lo, T. Wing; Lam, Sally Hing-po; Lee, Gabriel Kwun-wa (Frontiers in Psychiatry, 2018)
The present paper examines the issue of hidden drug abuse in Hong Kong. Although official statistics show that the reported number of drug-abuse cases has been in decline in recent years, it has been reported that drug abusers tend to hide themselves at home to take drugs; thus, they are not discovered easily by the law enforcement and social control agents who report drug abuse cases to the Central Registry of Drug Abuse, resulting in the decrease in the reported number of drug-abuse cases. This “dark figure” phenomenon is a reflection of the official figure and reporting behavior, not the actual situation of drug abuse in Hong Kong. Through in-depth interviews of 30 ex-drug addicts, the majority of them started drug taking in early youth, the present paper identifies five stages of drug taking from social acquaintance to social isolation. It argues that although drug taking among abusers is a kind of social activity in their initial stage of drug use, they become socially isolated when their drug use is prolonged. Several reasons are identified, including users’ easy accessibility to drugs and changes in the popularity of drugs and use of drug equipment. Most importantly, the hidden process is triggered and aggravated by numerous negative drug effects, such as decline in physical health, weak physical appearance leading to self-perceived discrimination, co-occurrence of psychiatric symptoms of increased anxiety and suspicion, and decline of trust among peers due to prolonged drug abuse. Possible solutions associated with clinical interventions, legislative policies, and law-enforcement operations are proposed.